2010
DOI: 10.1128/mcb.00900-09
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Copper Chaperone CCS by XIAP-Mediated Ubiquitination

Abstract: In order to balance the cellular requirements for copper with its toxic properties, an elegant set of mechanisms has evolved to regulate and buffer intracellular copper. The X-linked inhibitor of apoptosis (XIAP) protein was recently identified as a copper-binding protein and regulator of copper homeostasis, although the mechanism by which XIAP binds copper in the cytosol is unclear. Here we describe the identification of the copper chaperone for superoxide dismutase (CCS) as a mediator of copper delivery to X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 70 publications
0
57
0
1
Order By: Relevance
“…Brady et al (36) showed that, depending on the intracellular copper status, CCS delivers copper either to SOD1 or to XIAP. Under basal conditions, XIAP enhances copper acquisition and delivery to SOD1 by promoting the nondegradative ubiquitination of CCS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brady et al (36) showed that, depending on the intracellular copper status, CCS delivers copper either to SOD1 or to XIAP. Under basal conditions, XIAP enhances copper acquisition and delivery to SOD1 by promoting the nondegradative ubiquitination of CCS.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in pEBB-CCS-FLAG were introduced by the QuickChange site-directed mutagenesis method (Stratagene, primer sequences indicated in supplemental Table 2). pEBB-CCS-GST deletion constructs were kindly obtained from Dr. C. Duckett (Ann Arbor, MI) and described previously (36). A pSUPER-RETRO vector encoding short hairpin RNAs (shRNAs) against COMMD1 (shCOMMD1) was described previously (15,18).…”
Section: Methodsmentioning
confidence: 99%
“…It is unclear how SOD1 is able to influence survival pathways in lung cancer cell lines to permit growth. Recently, it was shown that the antiapoptotic protein XIAP (X-linked inhibitor of apoptosis) can activate SOD1 by ubiquitinating and activating the copper chaperone for superoxide dismutase (CCS), which delivers copper to SOD1, thereby enhancing its enzymatic function (17). It remains to be determined whether a similar process occurs in cancer cells, because the XIAP study was done in mammalian cell lines that were not derived from tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Protein Identification by Tandem LC/MS-MS-Standard protocols for in-gel digestion followed by mass spectrometry were carried out as described (39). The lanes were excised into 14 equal sized slices and destained with 30% methanol for 4 h. After reduction (10 mM DTT) and alklylation (65 mM iodoacetamide) of the cysteines at room temperature for 30 min, proteins were digested overnight with trypsin (Promega).…”
Section: Methodsmentioning
confidence: 99%